(untitled) (Economic and Political Thought, 2010)
The article aims at presenting benefits and advantages of bank products available to a retail customer. The author attempts to prove that the recent two years of the economic crisis, which was a result of financial institutions employees’ misappropriation, also resulted in the lack of customers’ openness to innovative financial products. A positive aspect of the whole situation is a closer and closer perspective of the end of the crisis and some hope that bad experiences will be transformed into greater caution and interest in acquiring knowledge. The article was based on the commonly available domestic literature dealing with the issue of banking in Poland and two foreign sources on investment. It turned out that another important aspect was the use of Internet resources and the author’s practical expertise which enabled the presentation of the newest trends in the Polish banking system.